Pengelolaan Lembaga Pemasyarakatan Oleh Perusahaan Swasta di Indonesia Studi Perbandingan Dengan Negara Amerika Serikat - Amin, Khairul; Oktavia, Maria One (UNES Law Review, 2024)
The existence of criminal law is part of the national law that organizes efforts to combat crime through the criminal justice system. Lapas plays a crucial role in the modern criminal justice system, with a focus on the rehabilitation of prisoners. The fact that Lapas is managed by the Indonesian state so far has never been rid of some problems such as overcapacity, inadequate facilities, and a lack of allocation of funds to operate prison facilities, which ultimately affects the quality of Lapas performance in Indonesia. This research using comparative legal methods to find out the similarities and differences among the elements of each legal system. The object of comparison is the State of the United States, which is administered in accordance with private parties. The results show that the Indonesian government has indeed issued a budget for the management of Lapas but has not been able to create an effective Lapas organization. Efforts that can be made by the government for future Lapas management can be achieved in cooperation with private companies in the framework of the development of Lapas infrastructure and funding sources, which are fundamental needs in order to efficiently manage Lapas.